2005
DOI: 10.1016/j.icesjms.2005.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Implications of climate change for the management of North Sea cod (Gadus morhua)

Abstract: Kell, L. T., Pilling, G. M., and O'Brien, C. M. 2005. Implications of climate change for the management of North Sea cod (Gadus morhua). e ICES Journal of Marine Science, 62: 1483e1491.Robustness of both short-term stock biomass recovery and longer-term sustainable management strategies to different plausible climatic change scenarios were evaluated for North Sea cod (Gadus morhua), where climate was assumed to impact growth and recruitment. In the short term, climate change had little effect on stock recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 25 publications
2
60
0
Order By: Relevance
“…5d). Impact of fishing mortality on size at maturity has been reported in other species such as cod from Irish and North Sea (Armstrong et al, 2004;Kell et al, 2005), however for Greenland cod no relationship was found between fishing intensity and length at age (Rätz and Lloret, 2005). Fishing activity usually removes larger individuals altering age and length composition of stocks that may result in selection of earlier maturing individuals (Olsen et al, 2004).…”
Section: Changes In Maturity Ogives In Response To Environmental Flucmentioning
confidence: 99%
See 2 more Smart Citations
“…5d). Impact of fishing mortality on size at maturity has been reported in other species such as cod from Irish and North Sea (Armstrong et al, 2004;Kell et al, 2005), however for Greenland cod no relationship was found between fishing intensity and length at age (Rätz and Lloret, 2005). Fishing activity usually removes larger individuals altering age and length composition of stocks that may result in selection of earlier maturing individuals (Olsen et al, 2004).…”
Section: Changes In Maturity Ogives In Response To Environmental Flucmentioning
confidence: 99%
“…Rose (2005) suggests that small pelagics respond quickly and strongly to climate changes because of their physiological limits and fast potential growth. Moreover, temperature may influence the fish maturation process indirectly through alterations of ecosystem composition, resource availability or hydrographic conditions (Kell et al, 2005;Orlova et al, 2005;Rätz and Lloret, 2005;Rose, 2005). The upwelling process causes a rise of cold deep water rich in nutrients (Wooster et al, 1976;Fraga, 1981) during summer.…”
Section: Changes In Maturity Ogives In Response To Environmental Flucmentioning
confidence: 99%
See 1 more Smart Citation
“…However, scenarios with higher rates of temperature increase resulted in faster rates of decline. In a re-analysis by Kell et al (2005), the authors modelled the effect of introducing a 'cod recovery plan' (as being implemented by the European Commission), under which catches were set each year so that stock biomass increased by 30 % annually until the cod stock had recovered to around 150,000 tonnes. The length of time needed for the cod stock to recover was not greatly affected by the particular climate scenario chosen (and was generally around five to six years), although overall productivity was affected and spawning stock biomass (SSB) once 'recovered' was projected to be considerably less than would have been the case assuming no temperature increase (251,035 tonnes compared to 286,689 tonnes in 2015).…”
Section: Year-class Strength and Implicationsmentioning
confidence: 99%
“…For North Sea cod, for example, an evaluation of management strategies suggested that reduced fishing mortality is one of the most important steps toward rebuilding this overfished stock in both the short and long term, even under a changing climate (Kell et al, 2005). Approaches to reduce mortality could include quotas, effort and gear restrictions, and technical measures to reduce bycatch of juveniles in multispecies fisheries.…”
Section: Addressing Cumulative Impactsmentioning
confidence: 99%